Resource economics - Conrad, Jon M. (Cambridge ; New York : Cambridge University Press, 1999)
This book presents about resource economics: Basic concepts; Solving numerical allocation problems; The economics of fisheries; ...
Keywords: Economics; Microsoft Excel; Mathematical models; Microsoft Excel (Computer file); Natural resources -- Management -- Mathematical models; Resource allocation -- Mathematical models